Assessing The Competencies Of Cellular Operations In Malaysia - Ngan Chong, Khoo (2007)
This research project develops a model framework and a survey instrument to investigate the relationship between service quality, network quality, customer satisfaction and customer loyalty. Results of the study provide the evidence that the proposed model framework perform reliably in the Malaysian cellular service setting.